Alteration in the expression of inflammatory parameters as a result of oxidative stress produced by moderate zinc deficiency in rat lung - Biaggio, Veronica Silvina (2010)
Suboptimal intake of dietary zinc (Zn) is one of the most common nutritional problems worldwide. Previously, the authors have shown that zinc deficiency (ZD) produces oxidative and nitrosative stress in lung of male rats. The goal of this study is to test the effect of moderate ZD on insulin-like growth factor (IGF)-1, IGF-binding protein (IGFBP)-5, NADH oxidase (NOX)-2, tumor necrosis factor alpha (TNFα), as well as the effect of restoring zinc during the refeeding period. Adult male rats were divided into 3 groups: Zn-adequate control group, Zn-deficient group, and Zn-refeeding group. eNOS, metallothionein (MT) II, and NOX-2 was increased in ZD group. The authors observed an increased gene transcription of superoxide dismutase (SOD)-2 and gluthathione peroxidase (GPx)-1 in ZD group, as well as in ZD-refeeding group, but catalase (CAT) transcription did not change in the treated groups. Proinflammatory factors, such as TNFα and vascular cell adhesion molecular (VCAM)-1 increased in ZD, whereas it decreased in ZD refeeding. However, peroxisome proliferator-activated receptor gamma (PPARγ) and IGF-1 gene transcription decreased in ZD, whereas IGFBP-5 decreased in the ZD group. These parameters are associated to alterations in the lung histoarchitecture. The zinc supplementation period is brief (only 10 days), but it is enough to inhibit some proinflammatory factors. Perhaps, zinc deficiency implications must be taken into account in health interventions because inflammation and prooxidant environment are associated with ZD in lung.